A terceirização e o trabalho escravo: coincidência? - Santos, Suely Rosa dos (2018)
This master thesis analyzes the relationship between outsourcing and labor in conditions analogous to those of slave labor in Brazil, in the light of the principle of human dignity. It aims to characterize contemporary slave labor and the profile of victims in the rural, civil construction and textile sectors, based on the parameters established by the international human rights treaties and the analysis of internal regulation. It evaluates the outsourcing and its evolution in Brazil from the internal regulation. It aims to demonstrate that the unlimited outsourcing introduced by the labor reform (Laws 13.429/2017 and 13.467 /2017) favors the practice of labor in conditions analogous to those of slave labor, violates the Federal Constitution of 1988 and international human rights treaties ratified by Brazil.